Pendidikan Islam di Indonesia Zaman Penjajahan Belanda dan Jepang - Ilham; Bahaking Rama; Muhammad Rusydi Rasyid (PIJAR: Jurnal Pendidikan dan Pengajaran, 2022)
Islamic education during the Japanese colonial era was closely related to mutual need. Japan needs Indonesian Muslims related to the Greater East Asia war, so that the Japanese side gets help from Indonesian Muslims. Meanwhile, Muslims hope that Indonesia's independence will be obtained. The Islamic education policy during the Japanese colonial era was essentially the same as that of the Dutch colonialists, it's just that the Japanese colonialists seemed a little softer than the Dutch colonial government. Maybe because of their presence on earth, Indonesia, which is still as old as corn, so they feel the need to ingratiate themselves with Muslims. It is undeniable that the education of the Dutch colonialists also brought benefits to the Indonesian people, especially to Muslims. Indigenous people are familiar with the modern education system, for example the class system, the use of blackboards, tables and benches. In terms of modern learning methods, and general knowledge. The other side of this colonial educational institution is that it promises more employment opportunities for students after they finish their studies.